Puerarin protects rat liver and kidney against cadmium-induced oxidative stress - WANG, JICANG; ZHU, HUALI; ZHANG, CAI; WANG, HONGWEI; YANG, ZIJUN; LIU, ZONGPING (The Indian Journal of Animal Sciences, 2019)
Oxidative stress is thought to be involved in cadmium (Cd) induced toxicity. This study examined the possible protective effect of puerarin on cadmium chloride (CdCl2, 2 mg/kg b.w.) induced toxicity in male rats. Male SD rats were treated with either intraperitoneal Cd and/or oral puerarin (100 mg/kg. b.w.) for 4 weeks. The results demonstrated that exposure to Cd led to an increase in the level of BUN, ALT and AST in serum. Cadmium raised the concentrations of MDA and GSH, and decreased antioxidants activities (SOD, CAT, and GSH-Px) in the liver and kidney. Conversely, administration of puerarin markedly attenuated Cd-induced biochemical alterations in serum, liver, and kidney tissues. These results suggest that puerarin exerts protective effects against Cd toxicity attributable to its antioxidant actions.